Do bioactive materials show greater retention rates in restoring permanent teeth than non-bioactive materials? A systematic review and network meta-analysis of randomized controlled trials - Fernandes, Juliana Benace [UNESP]; Contreras, Sheila Mondragón [UNESP]; da Silva Spinola, Manuela; Batista, Graziela Ribeiro; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP] (Springer Nature, 2024)
Objectives: To answer the following research question: does the clinical evaluation of restorations on permanent teeth with bioactive materials show greater retention rates than those with non-bioactive materials? Materials and methods: A search strategy was used in the following databases: MEDLINE via PubMed, Scopus, Web of Science, LILACS, BBO, Embase, The Cochrane Library, and OpenGrey. Randomized controlled trials (RCTs), with a minimum of 2-year follow-up and evaluating at least one bioactive material in permanent teeth were included. Risk of bias was detected according to the Cochrane Collaboration tool for assessing the risk of bias (RoB 2.0), and network meta-analysis was performed using a random-effects Bayesian-mixed treatment comparison model. Results: Twenty-seven studies were included. The success of the restorations was assessed using modified USPHS system in 24 studies and the FDI criteria in 3 studies. Network meta-analysis revealed three networks based on restoration preparations. Resin composites were ranked with higher SUCRA values, indicating a greater likelihood of being the preferred treatment for class I, II, and III restorations. In class V, resin-modified glass ionomer cement was ranked with the highest value. Conclusion: Bioactive restorative materials showed similar good clinical performance in terms of retention similarly to conventional resin composites. Clinical significance: The findings must be interpreted with caution because many RCT on restorative materials aim to verify the equivalence of new materials over the gold standard material rather than their superiority. The present systematic review also suggests that new RCT with longer follow-up periods are necessary.
Keywords: Bioactive materials; Dental caries; Dental restoration; Restorative materials; Systematic review